Reevaluating Human Gene Annotation: A Second-Generation Analysis of Chromosome 22 - Collins, John E.; Goward, Melanie E.; Cole, Charlotte G.; Smink, Luc J.; Huckle, Elizabeth J.; Knowles, Sarah; Bye, Jacqueline M.; Beare, David M.; Dunham, Ian

(untitled) (Genome Research, 2003)
We report a second-generation gene annotation of human chromosome 22. Using expressed sequence databases, comparative sequence analysis, and experimental verification, we have extended genes, fused previously fragmented structures, and identified new genes. The total length in exons of annotation was increased by 74% over our previously published annotation and includes 546 protein-coding genes and 234 pseudogenes. Thirty-two potential protein-coding annotations are partial copies of other genes, and may represent duplications on an evolutionary path to change or loss of function. We also identified 31 non-protein-coding transcripts, including 16 possible antisense RNAs. By extrapolation, we estimate the human genome contains 29,000–36,000 protein-coding genes, 21,300 pseudogenes, and 1500 antisense RNAs. We suggest that our revised annotation criteria provide a paradigm for future annotation of the human genome.[Supplemental material is available online at www.genome.org. The sequence data from this study have been submitted to GenBank under accession nos. AL009266, AL021682-3,AL021708, AL022729, AL035081-2, AL035364, AL035366, AL035545, AL049654,AL050253-8, AL050345-6, AL079310, AL096779-81, AL096879-81, AL096883,AL096886, AL138578, AL157851, AL159142-3, AL160111-2, AL160131-2,AL160311, AL355092, AL355192, AL355841, AL359401, AL359403, AL365511-5,AL442116, AL449243, AL449244, AL450314, AL589866-7, AL590120,AL590887-8, BU583989–BU585359. The following individuals kindly provided reagents, samples, or unpublished information as indicated in the paper: J. Seilhamer, L. Stuve, H. Roest-Crollius, A. Levine, G. Slater, and J. Kent.]